FAMILY PERCEPTION OF SCRAPING THERAPY AS AN ALTERNATIVE TO TRADITIONAL TREATMENT - Hidayah, Seventina Nurul; Harnawati, Riska Arsita; Andari, Istiqomah Dwi; Chikmah, Adevia Maulidya; Qudriani, Meyliya (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Scraping therapy, known locally as kerokan, is a traditional treatment still widely practiced in Indonesia to address minor ailments such as colds, muscle aches, and fever. Family perceptions strongly influence the preference for scraping therapy as a primary form of home care. This study aims to explore how families perceive scraping therapy as an alternative to modern medicine. A qualitative case study design was employed, involving participants who had received or administered scraping therapy in the past year, were aged 18 or older, and participated voluntarily. Purposive sampling was used to select participants. Data were collected through in-depth interviews and focus group discussions (FGDs), focusing on their knowledge, motivations, and personal experiences. Thematic analysis was conducted to identify key patterns and meanings. The findings revealed that many families consider scraping therapy effective, affordable, and easy to perform. It is viewed as a cultural tradition passed down through generations and a practical solution amid limited access to healthcare facilities. Nevertheless, some concerns were noted, including potential skin irritation and the absence of scientific validation. Despite these issues, cultural beliefs and accessibility make scraping therapy the preferred choice for minor health problems. Healthcare professionals should educate communities while respecting local traditions to ensure safe practices.